An Assessment of Economic and Financial Impacts of Jakarta-Bandung High-Speed Railway Project - Siddhartha Nath; Gusti Raganata (INDEF - Institute for Development of Economics and Finance, 2020)
In this paper, we assess the economic and financial impacts of the proposed Jakarta-Bandung high-speed railway project. Our assessment following Zou et. al. (2018) suggests that, over the long run, the project may increase the combined income of Jakarta, the neighbouring province Karawang and the country’s major industrial centre Bandung, by an estimated 12-18%, by increasing ‘market access’, by the firms in the region, under several assumptions. We estimated that the project will increase Indonesian real GDP by almost 0.4%, mostly during its construction phase, with certain assumptions on the returns to capital. On the other hand, although the project is expected to generate over 40,000 jobs in Indonesia, according to several sources, the project may entail an immediate loss of over 2,000 traditional jobs around the track. In addition, Transit Oriented Development plans, such as tourist spot in Walini, residential complex around the project site etc. are likely to affect community farming and water supply in the region. Therefore, we assessed that the success of the project is subjected to several legal and institutional barriers including ongoing issues related to the land acquisition. The sluggish progress of the project exerts financial risk to the stakeholders, especially since the project has no ‘guarantee’ from the Indonesian government. We estimated that the China Development Bank, as a majority fundraiser, bears a significantly large portion of the risk than the other stakeholders in the project. The financial risks faced by the Indonesian counterpart, on the other hand, is significantly lower. Keywords : High-speed rail, market access, economic growth, risks,